Between Technical-cultural Innovation by the Teutonic Order and Traditional Blacksmith Craftsmanship - Maciej Majewski (Fasciculi Archaeologiae Historicae, 2020)
The article starts with the description of a rare spur with hinged arms from Starogród in Culm Land, discovered during an excavation in 2018. The artifact is dated to the 2nd quarter of the 13th century and comes from the area of the probable first location of Chełmno. The main aim of the study is to describe and discuss the existing theories regarding the interpretation of this form of spurs. There are three main theories on the subject. The most probable one is that the arms with hinges were to serve for easier fixing of spurs on heavy boots and those with large decorations, such as belts or buckles. Due to the very early dating of the oldest spurs of this type, it should rather be said that spurs with hinges were used wherever it was found that it would facilitate their mounting on the leg. In none of the periods of occurrence, were these forms dominant but merely co-existed with those with rigid arms